2004
DOI: 10.1111/j.0736-8046.2004.21203.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin Diseases in Chinese Children at a Pediatric Dermatology Center

Abstract: Understanding the pattern of disease referrals is important in the delivery of a service. We followed 331 new referrals at a pediatric dermatology clinic over 12 months. Fifty percent of the patients were female; 293 patients (88.5%) had a single diagnosis and 36 (10.9%) had two diagnoses. Three leading causes for referrals accounted for 60% of the 371 skin diseases encountered: 124 diagnoses (33%) were of eczema, 73 diagnoses (20%) were of nevi, and 22 diagnoses (6%) were of viral warts. The nevi seen include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
45
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 6 publications
(7 reference statements)
13
45
3
Order By: Relevance
“…Another limitation also relates to subject selection for the TCM trial. The median (range) age of our patients was 11.3 (5-20) years, which is older compared with the respective data for new cases seen in our outpatient clinic (7.1 ± 4.4 years for boys and 7.5 ± 4.3 years for girls) [26]. Patients younger than 5 years of age were not recruited because of two reasons: these young patients were not able to swallow the TCM capsules and our pilot testing suggested that these children could not provide reliable responses to several CDLQI items including school and daily activities.…”
Section: Discussionmentioning
confidence: 51%
“…Another limitation also relates to subject selection for the TCM trial. The median (range) age of our patients was 11.3 (5-20) years, which is older compared with the respective data for new cases seen in our outpatient clinic (7.1 ± 4.4 years for boys and 7.5 ± 4.3 years for girls) [26]. Patients younger than 5 years of age were not recruited because of two reasons: these young patients were not able to swallow the TCM capsules and our pilot testing suggested that these children could not provide reliable responses to several CDLQI items including school and daily activities.…”
Section: Discussionmentioning
confidence: 51%
“…Similar observation has been seen in other studies conducted in referral hospitals. 1,13,15,19 The most common among congenital malformations in our study were capillary hemangioma (2.7% cases), followed by 1.2% cases of congenital melanocytic nevi and 0.8% cases of nevus depigmentoses. Hemangiomas occur in approximately 2.5% of all neonates.…”
Section: Discussionmentioning
confidence: 62%
“…Similar observations have been reported in other studies also. 1,4,9,11,12,15 Infectious and non-infectious nature of dermatoses depends upon many factors for e.g. type of population studied, location of study centre, climatic and socioeconomic factors, literacy etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] We report four cases of hair loss with unusual or extensive distribution and discuss the outcome of their management.…”
Section: Introductionmentioning
confidence: 99%